Estudio de tiempos y movimientos en el área de extrusión en la empresa CEDAL S.A. - Paredes Almeida, Edison Leonardo (2019)
The purpose of this research is to evaluate the productivity in the extrusion area of the “Corporación Ecuatoriana de Aluminio CEDAL S.A.”, in order to increase the productivity of the aluminium extrusion process, eliminating the bottlenecks that are used during profiling fabrication, through times and movements study. In the research the activities of the different jobs that form the extrusion process of profiles and the productive system were examine, by means of the survey of the real productivity information, later to propose an improvement proposal. In order to gather information from the proposed study, a field modality was adopted, using tools such as direct timing, documental revision and using the "promodel" software to evaluate the production system of the extrusion area. The obtained results allowed identifying the existing problem in an activity, which does not contribute in the fulfilment of the proposed productivity due to the fact that they present high times and a low utilization having a maximum yield in productivity of 800 to 910k / h. Next, a proposal is projected by means of a calculation that allows determining the ideal billet length for the matrices of high rotation present in the ABC of the year 2018. It is concluded that in the process there are bottlenecks due to a reduced use of the facilities generating aluminium waste, and therefore reducing the productivity required by the company. The use of a new work method, allows optimizing resources such as, raw material and machinery, giving an increase of the activities for the fulfilment of the proposed goals and the obtaining of quality products that satisfy the needs and requirements of the client.